On the Analytical Approach of Codimension-Three Degenerate Bogdanov-Takens (B-T) Bifurcation in Satellite Dynamical System (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we have conducted parametric analysis on the dynamics of satellite complex system using bifurcation theory. At first, fiveequilibrium points $ε_{0,1,2,3,4}$ are symbolically computed in which $ε_{1,3}$ and $ε_{2,4}$ are symmetric. Then, several theorems are stated and proved for the existenceof B-T bifurcation on all equilibrium points with the aid of generalized eigenvectors and practical formulae instead of linearizations. Moreover, a specialcase $α_2 = 0$ is observed, which confirms all the discussed cases belong to acodimension-three bifurcation along with degeneracy conditions.